Leucine‐rich repeat kinase 2 regulates Sec16A at ER exit sites to allow ER–Golgi export. (8th September 2014) - Cho, Hyun Jin; Yu, Jia; Xie, Chengsong; Rudrabhatla, Parvathi; Chen, Xi; Wu, Junbing; Parisiadou, Loukia; Liu, Guoxiang; Sun, Lixin; Ma, Bo; Ding, Jinhui; Liu, Zhihua; et al.
Abstract Leucine‐rich repeat kinase 2 (LRRK2) has been associated with Parkinson's disease (PD) and other disorders. However, its normal physiological functions and pathogenic properties remain elusive. Here we show that LRRK2 regulates the anterograde ER–Golgi transport through anchoring Sec16A at the endoplasmic reticulum exit sites (ERES). LRRK2 interacted and co‐localized with Sec16A, a key protein in the formation of ERES. Lrrk2 depletion caused a dispersion of Sec16A from ERES and impaired ER export. In neurons, LRRK2 and Sec16A showed extensive co‐localization at the dendritic ERES (dERES) that locally regulate the transport of proteins to the dendritic spines. A loss of Lrrk2 affected the association of Sec16A with dERES and impaired the activity‐dependent targeting of glutamate receptors onto the cell/synapse surface. Furthermore, the PD‐related LRRK2 R1441C missense mutation in the GTPase domain interfered with the interaction of LRRK2 with Sec16A and also affected ER–Golgi transport, while LRRK2 kinase activity was not required for these functions. Therefore, our findings reveal a new physiological function of LRRK2 in ER–Golgi transport, suggesting ERES dysfunction may contribute to the pathogenesis of PD.